Overexpression of ATP‐binding cassette transporters associated with sulfoxaflor resistance in Aphis gossypii glover. Issue 9 (15th May 2021) - Wang, Li; Zhu, Junshu; Cui, Li; Wang, Qinqin; Huang, Weiling; Ji, Xuejiao; Yang, Qingjie; Rui, Changhui
Abstract: BACKGROUND: Sulfoxaflor is a new insecticide for controlling against Aphis gossypii in the field. ATP‐binding cassette (ABC) transporters belong to a large superfamily of proteins and play an important role in the detoxification process. However, the potential role of ABC transporters in sulfoxaflor resistance in A. gossypii is unknown. RESULTS: In this study, an ABC transporter inhibitor, verapamil, dramatically increased the toxicity of sulfoxaflor in the resistant population with a synergistic ratio of 8.55. However, verapamil did not synergize sulfoxaflor toxicity in the susceptible population. The contents of ABC transporters were significantly increased in the Sul‐R population. Based on RT‐qPCR analysis, 10 of 23 ABC transcripts, ABCA1, ABCA2, ABCB1, ABCB5, ABCD1, ABCG7, ABCG16, ABCG26, ABCG27, and MRP7, were up‐regulated in the Sul‐R population compared to the Sus population. Meanwhile, inductive effects of ABCA1, ABCD1, ABCG7 and ABCG26 by sulfoxaflor were found in A. gossypii . Furthermore, knockdown of ABCA1 and ABCD1 using RNAi significantly increased the sulfoxaflor sensitivity in Sul‐R aphids. CONCLUSION: These results suggested that ABC transporters, especially the ABCA1 and ABCD1 genes, might be related with sulfoxaflor resistance in A. gossypii . This study will promote further work to validate the functional roles of these ABCs in sulfoxaflor resistance and might be helpful for the management of sulfoxaflor‐resistant A. gossypii . Abstract : Overexpression of ATP‐binding cassette transporters associated with sulfoxaflor resistance in Aphis gossypii © 2021 Society of Chemical Industry.